OsTDL1A binds to the LRR domain of rice receptor kinase MSP1, and is required to limit sporocyte numbers - Zhao, Xinai; De Palma, Justina; Oane, Rowena; Gamuyao, Rico; Luo, Ming; Chaudhury, Abdul; Hervé, Philippe; Xue, Qingzhong; Bennett, John (Wiley, 2008)
Hybrids lose heterotic yield advantage when multiplied sexually via meiosis. A potential alternative breeding system for hybrids is apospory, where female gametes develop without meiosis. Common among grasses, apospory begins in the nucellus, where aposporous initials (AIs) appear near the sexual megaspore mother cell (MeMC). The cellular origin of AIs is obscure, but one possibility, suggested by the mac1 and msp1 mutants of maize and rice, is that AIs are apomeiotic derivatives of the additional MeMCs that appear when genetic control over sporocyte numbers is relaxed. MULTIPLE SPOROCYTES1 (MSP1) encodes a leucine‐rich‐repeat receptor kinase, which is orthologous to EXS/EMS1 in Arabidopsis. Like mac1 and msp1, exs/ems1 mutants produce extra sporocytes in the anther instead of a tapetum, causing male sterility. This phenotype is copied in mutants of TAPETUM DETERMINANT1 (TPD1), which encodes a small protein hypothesized to be an extracellular ligand of EXS/EMS1. Here we show that rice contains two TPD1‐like genes, OsTDL1A and OsTDL1B. Both are co‐expressed with MSP1 in anthers during meiosis, but only OsTDL1A and MSP1 are co‐expressed in the ovule. OsTDL1A binds to the leucine‐rich‐repeat domain of MSP1 in yeast two‐hybrid assays and bimolecular fluorescence complementation in onion cells; OsTDL1B lacks this capacity. When driven by the maize Ubiquitin1 promoter, RNA interference against OsTDL1A phenocopies msp1 in the ovule but not in the anther. Thus, RNAi produces multiple MeMCs without causing male sterility. We conclude that OsTDL1A binds MSP1 in order to limit sporocyte numbers. OsTDL1A‐RNAi lines may be suitable starting points for achieving synthetic apospory in rice.